THE STUDY OF AIRBNB DEVELOPMENT DYNAMICS AND THE EFFECT OF ITS PROXIMITY TO HOTEL TOWARDS AIRBNB'S OCCIPANCY RATE - Nathasya, Tengku
The development of sharing economy provides benefits as well as threats to the community, such as Airbnb. Airbnb helps provide people with additional income from rooms in their house that were not previously utilized. On the other hand, Airbnb also has the potential to eliminate jobs that were previously created by hotels. This problem is increasingly significant in cities where employment is depending on hotels, such as Bandung. Therefore, we need a study that discusses the Airbnb competition with hotels. This study can be used as a consideration for the government in formulating policies in order to capture the benefits of Airbnb's sharing economy to the community without marginalizing the existence of the hotel itself. This study uses descriptive and spatial analysis methods to identify patterns of Airbnb development, then uses analysis of service coverage to identify the proximity of locations between Airbnb and hotels. Then a regression analysis is used to identify the effect of its proximity towards Airbnb's occupancy rate. The results of this study indicate that there is competition between Airbnb listings and adjacent hotels in Bandung. However, not all types and classes of hotels compete with Airbnb listings. Only 2-star, 4-star, 5-star and resort hotels that compete with Airbnb in Bandung, and 2-star, 4-star and hotel resorts within the hot spots, which compete with Airbnb.